Phencyclidine receptors in porcine coronary artery - Shi Gang-Gang; Xu Shao-Fen (Acta Pharmacologica Sinica; Vol 14, No 1 (January 1993): Acta Pharmacologica Sinica, 2016)
By using radioligand assay, there was a phencyclidine (Phe) binding site in porcine coronary artery. This binding was specific, reversible, saturable, and stereoselective. The Scatchard analysis showed that the binding site was a single class, with dissociation constant (Kd) and maximum binding (Bmax) of 27.7 +/- 6.9 nmol.L-1 and 0.82 +/- 0.15 pmol/mg protein, respectively. The displacement experiments revealed that the [3H]Phe binding was displaced by nonradioactive Phe, TCP (Phe receptor agonists), and dextrophan (its antagonist). d-INN, a ligand of sigma receptor, had a weaker activity of displacement. These showed a dose-dependent manner. Both etorphine, an agonist of opioid receptor, and N-methyl-D-aspartic acid (NMDA), an excitatory amino acid, failed to displace the binding. These results suggest that the Phe receptors exist in the porcine coronary artery.